The identities of insulin signaling pathway are affected by overexpression of Tau and its phosphorylation form - Ma, Ningtian; Liang, Yuyang; Yue, Lingyun; Liu, Pu; Xu, Yuxia; Zhu, Cuiqing (Frontiers in Aging Neuroscience, 2022)
Introduction Hyperphosphorylated Tau formed neurofibrillary tangles was one of the major neuropathological hallmarks of Alzheimer’s disease (AD). Dysfunctional insulin signaling in brain is involved in AD. However, the effect of Tau pathology on brain insulin resistance remains unclear. This study explored the effects of overexpressing wild-type Tau (WTau) or Tau with pseudo-phosphorylation at AT8 residues (PTau) on the insulin signaling pathway (ISP). Methods 293T cells or SY5Y cells overexpressing WTau or PTau were treated with or without insulin. The elements in ISP or the regulators of IPS were analyzed by immunoblotting, immunofluorescent staining and co-immunoprecipitation. Akt inhibitor MK2206 was used for evaluating the insulin signaling to downstream of mTOR in Tau overexpressing cells. The effects of anti-aging drug lonafarnib on ISP in WTau or PTau cells were also analyzed with immunoblotting. Considering lonafarnib is an inhibitor of FTase, the states of Rhes, one of FTase substrate in WTau or PTau cells were analyzed by drug affinity responsive target stability (DARTS) assay and the cellular thermal shift assay (CETSA). Results WTau or PTau overexpression in cells upregulated basal activity of elements in ISP in general. However, overexpression of WTau or PTau suppressed the ISP signaling transmission responses induced by insulin simulation, appearing relative higher response of IRS-1 phosphorylation at tyrosine 612 (IRS-1 p612) in upstream IPS, but a lower phosphorylation response of downstream IPS including mTOR, and its targets 4EPB1 and S6. This dysregulation of insulin evoked signaling transmission was more obvious in PTau cells. Suppressing Akt with MK2206 could compromise the levels of p-S6 and p-mTOR in WTau or PTau cells. Moreover, the changes of phosphatases detected in WTau and PTau cells may be related to ISP dysfunction. In addition, the effects of lonafarnib on the ISP in SY5Y cells with WTau and PTau overexpression were tested, which showed that lonafarnib treatment resulted in reducing the active levels of ISP elements in PTau cells but not in WTau cells. The differential effects are probably due to Tau phosphorylation modulating lonafarnib-induced alterations in Rhes, as revealed by DARTS assay. Conclusion and discussion Overexpression of Tau or Tau with pseudo-phosphorylation at AT8 residues could cause an upregulation of the basal/tonic ISP, but a suppression of insulin induced the phasic activation of ISP. This dysfunction of ISP was more obvious in cells overexpressing pseudo-phosphorylated Tau. These results implied that the dysfunction of ISP caused by Tau overexpression might impair the physiological fluctuation of neuronal functions in AD. The different effects of lonafarnib on ISP between WTau and PTau cells, indicating that Tau phosphorylation mediates an additional effect on ISP. This study provided a potential linkage of abnormal expression and phosphorylation of Tau to the ISP dysfunction in AD.